Pseudomonas spp. causing spoilage in Brazilian cheeses by pigment production - Rodrigues, Rafaela da Silva (2022)
Cheeses are foods prone to the growth of spoilage microorganisms, such as Pseudomonas: one of the most complex and diverse genera of Gram-negative bacteria, which makes it difficult to correctly assign strains to the species. Reports in recent years have shown that some strains belonging to this genus are capable of producing a blue pigment that is diffusible in dairy products with a high moisture content, in cold storage. Therefore, research has tried to elucidate aspects related to the production of this pigment, as well as the genomic region related to this phenotype, however there are still contradictions between their results. Here, we identified blue pigment-producing Pseudomonas strains isolated from spoiled samples of Minas Frescal cheese and processed cheese “requeijão em barra”, and used whole-genome sequencing (WGS) and bioinformatics tools to aid in the studies. For the first time, Pseudomonas strains that cause blue discoloration in Brazilian cheeses were investigated and identified. We found Pseudomonas carnis and Pseudomonas paracarnis as pigment producers, with rapid production at refrigerated temperatures and at 25 °C. Strains obtained here are phylogenetically related to others already investigated in other countries, and bioinformatics analysis helped to identify a genomic region of 74 genes, contained only in pigment producers, which includes tryptophan biosynthesis genes (trpABCDF) and genes for mobile genetic elements (MGE) such as genes involved in horizontal gene transfer (e. g., pilM, pilV, pilX, tadA, traD). This region has also been identified by bioinformatics tools as an integrative and conjugative element (ICE), due to components related to conjugative-transposon-like mobile genetic elements and it has plasmid- like conjugative properties. Furthermore, a phylogenomic investigation of strains confirmed as P. carnis, deposited in GenBank, showed that there is no evolutionary relationship between those that are pigmenting and carriers of duplicated trpABCDF genes, all of which are isolated only from food. With this, it appears that the recent spoilage in food reported in different countries may not have been caused by the spread of a single strain. Therefore, studies like this help to understand an issue that is affecting different nationalities, as well as providing a basis for the development of markers that will allow the tracking and control of these spoilers in food.In addition, it shows that a correct bacterial identification at the species level is essential for a reliable execution of investigations, when it comes to Pseudomonas. Keywords: Pseudomonas. Spoilage. Blue discoloration. Genomic analysis.